Association of TLR4 expression and genomic instability with renal function markers in diabetic nephropathy - Ayat Rasheed Hameed; Rasha Salih Nuhair (Počki, 2025)
Background. Diabetic nephropathy is a serious side effect of both type 1 and 2 diabetes mellitus. Toll-like receptor 4 (TLR4), the first identified and most extensively studied member of the TLR family, has been implicated in the development of various renal diseases such as acute kidney injury, renal ischemia-reperfusion injury, and glomerulonephritis. The purpose of this study was to assess the expression of TLR4 in relation to inflammation in diabetic patients with and without renal failure, to discuss the role of these receptors in the development of diabetic nephropathy, and to highlight chromosomal, nuclear, and biochemical changes (urea and creatinine) in patients with renal failure and diabetes. Materials and methods. The dialysis unit housed 40 healthy controls, 40 patients with diabetic mellitus, 40 with nephropathy, and 40 with diabetic nephropathy. This study was conducted from October 2024 to January 2025. Blood samples (5 ml) were collected from patients and healthy individuals and distributed into tubes for gene expression, chromosomal aberration, and micronucleus frequency, the remaining — to evaluate the renal function. Results. Participants with nephropathy and diabetic nephropathy have significantly higher TLR4 gene expression in their blood than healthy individuals. Patients with diabetes, nephropathy, or diabetic nephropathy were found to have more micronuclei and chromosomal aberrations. Significantly increased serum urea and creatinine levels have also been observed in patients with nephropathy and diabetic nephropathy. Conclusions. TLR4 expression increases: the percentage is lowest in healthy people (3.927), higher in diabetic (18.31), and nephropathy patients (17.352), and highest in those with diabetic nephropathy (27.158). Chromosomal abnormalities are associated with diabetic nephropathy and impaired renal function.